Short-term report of early glaucoma surgery with a clear lens extraction and an intraocular lens, OMNI canaloplasty, and a HYDRUS microstent: a case series in younger patients - Laroche, Daniel; Desrosiers, Abelard; Ng, Chester (Frontiers in Ophthalmology, 2024)
The purpose of this case series is to report the surgical outcomes from the combination of clear lensectomy, omni canaloplasty and Hydrus microstent with adjacent goniotomy.Methods: This is a retrospective non-comparative single center case series of 4 Black patients of African descent, with glaucoma who underwent clear lensectomy, omni canaloplasty and Hydrus microstent with adjacent goniotomy. The surgeries were performed by experienced cataract and glaucoma surgeon Daniel Laroche, MD. The parameters investigated in this study were postoperativepost operative intraocular pressure (IOP) and mean preoperative and postoperative medications.The mean age of all 4 patients was 44.5 years old. All patients had a mean reduction of IOP from 17mmHg to 12.7mmHg post-operatively. The mean preoperative medications were 2.2 while and post operative was 0.3. Potential complications such as hyphema, IOP spikes, or corneal edema, were not seen in this series. All patients achieved lower intraocular pressure and stable vision with less refractive error. Patients also experienced improved visual fields, clearer vision, and more open angles.Black people receive cataract surgery 30% less than white patients in America and globally have decreased access to cataract surgery due to the history of slavery and colonialism. Clear lensectomy and combined microinvasive glaucoma surgery (MIGS) in patients with primary open angle glaucoma (POAG) and narrow angle glaucoma (NAG) results in excellent safely lowering of IOP and has an excellent safely.ty profile. Limitations of this study include small series, and retrospective potential for bias. Further research with a larger series and prospective trial should be performed with follow-up.